Surgical Margin Determination in the Era of HPV‐Positive Oropharyngeal Cancer. (1st April 2021) - Pool, Christopher; Weaver, Taelor; Zhu, Junjia; Goldenberg, David; Goyal, Neerav
Abstract : Objectives/Hypothesis: The goal of head and neck cancer surgery is the complete resection of tumor with a cuff of healthy tissue. A 5‐mm margin is optimal but not always achievable in the oropharynx. We aimed to identify a consensus of definition and management of close margins for human papilloma virus (HPV)‐associated oropharyngeal cancer without other risk factors. Study Design: Descriptive survey. Methods: A survey of the American Head and Neck Society (AHNS) was conducted to evaluate the abovementioned objectives by presenting hypothetical scenarios and asking questions regarding management. Results: One‐hundred fifty‐five AHNS members completed the survey (18% response rate). Close margins were defined as <5 mm, <3 mm, and <1 mm by 27.7%, 32.3%, and 32.3% of respondents. There was no significant difference in margin determination with experience level ( P  = .186). In an HPV‐positive tumor with close margins, 51% chose postoperative observation. The remainder chose adjuvant radiation (22.6%), chemoradiation (1.9%), or re‐excision of the wound bed (19.4%). There was no association between postoperative close margin management and experience level ( P  = .80). Conclusion: Heterogeneity exists in the definition and management of close margins in HPV‐mediated oropharyngeal carcinoma (OPSCC). Establishing a standard regarding close margins in HPV‐mediated OPSCC may allow for the optimization of outcomes and help define best practices. Level of Evidence: 5 Laryngoscope, 131:E2650–E2654, 2021